1970
DOI: 10.1111/j.1423-0410.1970.tb01477.x
|View full text |Cite
|
Sign up to set email alerts
|

An Erroneous Exclusion of Paternity in a Chinese Family Exhibiting the Rare MNSs Gene Complexes Mk and MsIII

Abstract: Because of an apparent exclusion of paternity of the type father M/child N, and of the father's insistent denial of this exclusion, a thorough investigation of the MNSs groups of a Chinese family was carried out. The 'cxctusion' was proved false by the demonstration of Mk in the persons involved. It is the first time that this rare gene comes to notice through disputed paternity, and this is the first example of M k in Chinese. The family also had several members possessing Ms"', a gene complex which produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…It was concluded that these 'weak N' Mi-III react weakly only with animal anti-N but not at all with potent human anti-N. This finding confirmed the observation which was first mentioned by Sturgeon et al [8]. …”
Section: Investigation Of Red Cell Antigenssupporting
confidence: 81%
“…It was concluded that these 'weak N' Mi-III react weakly only with animal anti-N but not at all with potent human anti-N. This finding confirmed the observation which was first mentioned by Sturgeon et al [8]. …”
Section: Investigation Of Red Cell Antigenssupporting
confidence: 81%
“…The latter two, in addition to being Mi(a+), were shown to be Vw-Mur+ Hil+ and thus to belong to Miltenberger cell class III (Mi-III) according to the scheme proposed by Cleghorn [4]. The five M Mi(a+) samples in the first series of tests may also be safely considered as Mi-III, since their weak reaction with rabbit anti-N is characteristic of this class in blood of type M [4,5,9]. Three Mi(a+) samples of type MN were found, one in the first and two in the second part of the study: since the latter two were shown to belong to class Mi-III, the same has been assumed for the first.…”
Section: Serological Tests and Resultsmentioning
confidence: 99%
“…One of these two sera was of human, the other of rabbit origin, and the M bloods referred to gave negative reactions with the first, but positive ones with the second, although these were distinctly weaker than the reactions obtained with type MN bloods. In a large Chinese family, in whidi extensive MNSs tests were being performed, several members showing this peculiarity were all found to be Miltenberger positive [9]. This prompted us to study the frequency of Mia in Chinese and its association with the 'variant N' defined above.…”
mentioning
confidence: 99%
“…Genotypes of mating l-1x I-2: The same applies to matings 1-1 x 1-2 and II-l x II-2 in the pedigree published by Sturgeon et al [13]. The issue of these 17 Mk x non-Mk matings comprises 64 children, 6 of which are omitted from the following counts as being Mk propositi.…”
Section: The Children Of Matings Of Known or Presumed Type Mk X Non-mklmentioning
confidence: 99%
“…One expects such a gene to occur in half of the children of a mating in which one partner possesses it and the other does not. It is the purpose of the present paper to analyze the data provided by the 6 Mk families investigated by us so far, together with those from 2 other informative Mk families reported by Henningsen [4] and by Sturgeon and co-workers [13], and to show that the distribution of Mk children from the type of mating defined above is as expected. A few comments on so-called anti-Mk sera are also included and the possible nature of the Mk gene will be discussed.…”
mentioning
confidence: 99%